Subjective and Oxytocinergic Responses to Mindfulness Are Associated With Subjective and Oxytocinergic Responses to Sexual Arousal - Dickenson, Janna A.; Alley, Jenna; Diamond, Lisa M. (Frontiers in Psychology, 2019)
Mindfulness – the ability to pay attention, on purpose, without judgment, and in the present moment – has consistently been shown to enhance women’s sexual arousal. As a first step toward understanding potential neuroendocrine underpinnings of mindfulness and sexual arousal, we examined whether individual differences in subjective and neuroendocrine (i.e., oxytocin) responses to mindful breathing were associated with individual differences in subjective and neuroendocrine responses to sexual arousal. To achieve this aim, 61 lesbian, bisexual, and heterosexual women completed a questionnaire assessing dispositional mindfulness, underwent an arousal task while continuously rating their sexual arousal and a mindful breathing task, after which participants reported on their ability to detect attentional shifts, and provided salivary samples after each assessment. Results indicated that women who were quicker to detect attentional shifts and women who reported greater sexual arousability exhibited larger changes (decreases) in oxytocin in response to mindful breathing and were the only women to exhibit increases in oxytocin in response to the sexual arousal induction. Results further indicated that individuals who exhibit greater subjective responsiveness to mindfulness and sexual arousal appear to have an oxytocinergic system that is also more responsive to both arousal and to mindfulness. These results make a significant contribution to our understanding of the role of attentional processes in sexual arousal, and warrant future examination of oxytocin as a potential neuroendocrine mechanism underlying the link between mindfulness and sexual arousal.